The region of Murcia in secondary education textbooks. A narrative in the shadow of Spain and Europe - Rodríguez Pérez, Raimundo A.; Simón García, María del Mar; Molina Puche, Sebastián (Historia y Memoria de la Educación, 2017)
Social science textbooks are the most widely read historical narrative, and for much of the population constitute the only reading they will ever have done on the subject . Hence the need to analyze in detail what types of content and activities these books contain. The pre-eminence of textbook as the main educational resource in Spain remains overwhelming, both in primary and secondary education. This derives from the conceptual model assigned to humanistic subjects like history. Along with the lecture and rote examination, the manual gives us a picture of the advances and setbacks in the teaching of history in Spain. While studies on issues regarding national identity and narrative are abundant, there is a conspicuous lack of coverage in the manuals of the different autonomous communities since educational power was transferred to them. In both quantitative and qualitative terms, the relevance given to the regions is far inferior to that given to state and universal contents (Eurocentric), and the latest laws have only led to more of a setback. Our examination of the case of the Region of Murcia seeks to reveal the continuity of clichés that simplify and distort the history of this territory, preventing students from acquiring a minimum background knowledge of the region’s diversity of landscapes, cultures and lifestyles. To this end we have analyzed nine history textbooks of the 1st, 2nd and 4th years of Secondary Education, covering the last two decades and three most recent education laws (LOGSE, LOE and LOMCE).